Expert consensus on best evaluative practices in community-based rehabilitation. Issue 5 (27th February 2016) - Grandisson, Marie; Thibeault, Rachel; Hébert, Michèle; Cameron, Debra
Abstract: Purpose : The objective of this study was to generate expert consensus on best evaluative practices for community-based rehabilitation (CBR). This consensus includes key features of the evaluation process and methods, and discussion of whether a shared framework should be used to report findings and, if so, which framework should play this role. Method : A Delphi study with two predefined rounds was conducted. Experts in CBR from a wide range of geographical areas and disciplinary backgrounds were recruited to complete the questionnaires. Both quantitative and qualitative analyses were performed to generate the recommendations for best practices in CBR evaluation. Results : A panel of 42 experts reached consensus on 13 recommendations for best evaluative practices in CBR. In regard to the critical qualities of sound CBR evaluation processes, panellists emphasized that these processes should be inclusive, participatory, empowering and respectful of local cultures and languages. The group agreed that evaluators should consider the use of mixed methods and participatory tools, and should combine indicators from a universal list of CBR indicators with locally generated ones. The group also agreed that a common framework should guide CBR evaluations, and that this framework should be a flexible combination between the CBR Matrix and the CBR Principles. Conclusions : An expert panel reached consensus on key features of best evaluative practices in CBR. Knowledge transfer initiatives are now required to develop guidelines, tools and training opportunities to facilitate CBR program evaluations. Implications for Rehabilitation: CBR evaluation processes should strive to be inclusive, participatory, empowering and respectful of local cultures and languages. CBR evaluators should strongly consider using mixed methods, participatory tools, a combination of indicators generated with the local community and with others from a bank of CBR indicators. CBR evaluations should be situated within a shared, but flexible, framework. This shared framework could combine the CBR Matrix and the CBR Principles.